Symposium 10: Challenges and Potentials for Institutional and Technological Infrastructures in Adopting Social Media - Ryberg, Thomas (Proceedings of the International Conference on Networked Learning, 2008)
Since late 2004 where the term web 2.0 was initially coined, the concept has generated huge attention and debate. The term web 2.0 has become gradually more popular (and more obnoxious some would argue) during the period from the last months of 2005 until now. The terms have slowly pervaded academic discourse and the notion of 2.0 has also travelled to other spheres than technology and become quite widespread across a number of different and unrelated sectors. While the web 2.0 movement has certainly been fuelled by powerful forces and internet businesses, it has also had its opponents framing web 2.0 as a meaningless buzz or business term. Most noticeably Tim Berners-Lee who called it a 'piece of jargon nobody knows what means'. Still, the force and speed with which the 2.0 thinking has spread across a number of only loosely related domains signals that there is, if not a qualitative break or paradigm shift, then at least a disturbance of our regular ways of thinking about (and using) technologies for sharing, collaborating, learning and participating. These disturbances hold both challenges to, but also potentials for institutional and technological infrastructures within the domain of education. The paper will argue that there are some tensions and contradictions between on the one hand an institutional perspective, institutional technological infrastructures and then on the other hand the emerging educational and institutional interests in social media or web 2.0 'technologies'. The tensions and potentials are explored through relating the web 2.0 technologies and social media with sociological trends adopted from Castells (2001) and Wenger (2005). From this it is argued that social software, social media and web 2.0 tools and services can be seen as a materialisation and radicalisation of the sociological trends of networked individualism, the individualization of trajectories of identity and the horisontalisation of knowledge. The constant traversing of different types of networks and the sharing, copying and reuse of resources across ego-centric and object-centric social networks, which is a characteristic of web 2.0, reflects the material radicalisation of these trends. Simultaneously, the horisontalisation of knowledge as a sociological trend challenges vertical, hierarchical and institutionalised conceptions of knowledge - a pattern that seems to be further aggravated by the implicit understanding of knowledge contribution and sharing within a web 2.0 context which runs counter to institutional views of what constitute valid knowledge contributions From the perspective of technological infrastructures, an incorporation of web 2.0 and social software is not only a matter of adopting new technologies, but equally concerns the interaction between, technological, pedagogical and organisational understandings of practice and knowledge. Due to the tensions and contradictions between institutions and web 2.0 practices, the paper argues that the 'interface'between institutions, teachers and students in form of the networks, the nature of shared content and the management of identity need to be carefully negotiated in adopting web 2.0 technologies and social software as part of institutional technological infrastructures. This paper would also suggest that these tensions and contradictions cannot really be resolved in advance, but are tensions and contradictions that must be dynamically negotiated as part of the ongoing pedagogical, organisational and technological practices which form the components of institutional technological infrastructures.